Cell Biology of Herpes Viruses - Osterrieder, Klaus (Springer International Publishing : Imprint: Springer, 2017)
Herpes viruses are widely distributed in nature, causing disease in organisms as diverse as bivalves and primates, including humans. Each virus appears to have established a long-standing relationship with its host, and the viruses have the ability to manipulate and control the metabolism of host cells, as well as innate and adaptive antiviral immune responses. Herpes viruses maintain themselves within hosts in a latent state resulting in virus persistence for years - usually for the life span of the hosts. Herpes viruses comprise a large number of pathogens with diverse cellular targets and biological consequences of infection. What they have in common is their structure and the fact that they establish a dormant (latent) infection in their hosts that usually persists for life. The reviews here will highlight the general principles of herpes virus infection, with equal attention to overall principle and important difference. Also, the cell type- and life-style dependent differences in the establishment and maintenance of virus persistence will be covered.
Keywords: Medicine.; Immunology.; Virology.; Cell biology.; elektronické knihy; electronic books